Fixation of comminuted midshaft clavicle fractures with bone fragments separated by soft tissue using a novel double ligature technique: A case report. Issue 45 (November 2017) - Ju, Wei-Na; Wang, Cheng-Xue; Wang, Tie-Jun; Qi, Bao-Chang
Abstract: Rationale: Clavicle fractures are common, and mostly occur in the midshaft. Methods for operative treatment of midshaft clavicle fractures are evolving, as they improve clinical outcomes compared with traditional conservative management. However, fixation of comminuted midshaft clavicle fractures with bone fragments separated by soft tissue remains a challenge. Patient concerns: Here, we present a case of comminuted midshaft clavicle fracture with a bone fragment separated from the main fracture by soft tissue. Diagnosis: Left comminuted midshaft clavicle fracture. Interventions: We treated this patient with a novel double ligature technique using absorbable suturing. Outcomes: In the past 7 years, we have treated >50 patients with this technique. We have achieved good clinical outcomes with no complications. Lessons: We recommend widespread use of our novel double ligature technique for treating comminuted midshaft clavicle fractures with bone fragments separated by soft tissue.